Dyeability of Red Cabbage Colorant on Silk Fabric Treated With Entada Spiralis Extracts - Mat Shom, N.; I.A. Kadir, M.; R. Ahmad, M. (International Journal of Engineering and Technology, 2019)
Of late, dyeing fabrics with natural colorants have been the attention of the industry. Natural colorants especially from plants have the advantage of being friendly towards the environment as the extraction, processing and dyeing procedures are considered green and safe. However, most natural dyes have poor colourfastness and needed mordants to improve their dyeability. In this study, the addition of Entada spiralis was utilized as a surface modifier to improve dyeability on 100% silk fabrics using extracts from red cabbage. The plant serves as a surface-active agent to reduce the surface tension of the fabrics. The surfactant is also a natural resource and therefore is not harmful to the environment. The Entada spiralis was extracted through boiling for 30 minutes on a hot plate before treating the extracts on the fabrics. During dyeing, lime was used as the mordant simultaneously with dyeing. The dyed fabrics were evaluated for colorfastness to washing, rubbing/crocking and perspiration using the Gray Scale Standard. In addition, the dyed fabrics were also measured for their colour strength, colour coordinates and % reflectance. The results showed that dyed fabrics with Entada spiralis have darker shades in comparisons with the untreated fabric.Â Â